A case of mesangioproliferative glomerulonephritis(GN) associated with unique lesions of juxtaglomerular apparatus (JGA) and interstitium - YONESHIMA, HIDEO; TAKEUCHI, MASASHI; MATSUNOBU, SEIICHI; KITAMURA, HIROSHI; SHIMIZU, AKIRA; HAYAMA, NAOAKI; KURIHARA, SATOSHI; YAMANAKA, NORIAKI; SAKURAI, YUSEI; IINO, YASUHIKO (Nihon Jinzo Gakkai shi, 1993)
A case of mesangioproliferative glomerulonephritis (GN) associated with unique lesions of the juxtaglomerular apparatus (JGA) and interstitium is discussed. A 31-year-old Japanese woman who developed eyelid and pretibial edema with nephrotic-range proteinuria (4.8g/day) and without hematuria, was admitted. Her proteinuria and edema quickly disappeared within 7 days after admission without treatment. Her blood examinations revealed hypocomplementemia on admission, but complement recovered to normal levels after 4 weeks. A renal biopsy specimen obtained on the 5th day of admission revealed moderate mesangioproliferative GN with marked periarteriolar inflammatory cell infiltrations in the JGA and occasionally in the tubular interstitium. Depositions of IgG, IgA, IgM and C3 were observed in the glomerular mesangial regions and some capillary walls, but not in the extraglomerular areas. Titers of GN-related viral antigens were not increased. Although the renal histology of this case was similar to that of experimental acute cytomegalovirus (CMV) GN in mice (described by Smith, R. D.), we could not detect CMV antigen by indirect immunofluorescent method or the virus-like particles by electron microscopy. Clinical cases of nephropathy combining lesions of the glomerulus, JGA, and intersitium are very rare. We herein report a patient with mesangioproliferative GN, who underwent an acute clinical course associated with unique inflammatory lesions of the JGA and/or interstitium.